PSVI-17 Effect of Post-Ruminal Amino Acid Supply on Organ Mass and Small Intestinal Length in Holstein Bull Calves fed a Starch-Based Milk Replacer. (21st September 2022) - Petzel, Emily; Acharya, Subash; Bailey, Eric; Shiba, Setsabile; Brake, Derek
Abstract: Forty Holstein bull calves were fed 1 of 3 starch-based milk replacers for either 10 or 35 days to determine responses in organ mass and small intestinal length. Calves (87.2 ± 7.7 kg) were bottle-fed a cornstarch-based milk replacer (727 g of cornstarch daily) alone, milk replacer with added casein (154.7 g/d) or milk replacer with added glutamate (45.5 g/d) for 10 or 35 d. Prior to receiving treatments calves were fed a commercial milk replacer for either 12 or 15 weeks so that measures of organ mass and small intestinal length were collected at the same day of age. Measures of organ mass were achieved after calves were euthanized and digesta was removed. Duodenum was defined as the first 1-m caudal to the pyloric sphincter. Jejunum and ileum were defined as the cranial and caudal halves of the remaining small intestines. Data were analyzed using the MIXED procedure of SAS. Average daily gain was 68% greater (P = 0.02) for calves fed casein compared to control, but glutamate did not differ from casein or control. Mass of the omasum, abomasum, jejunum, ileum, heart, or kidney and length of the jejunum or ileum were not affected by treatment (P ≥ 0.18); however, additions of casein increased (P ≤ 0.05) mass of the rumen, duodenum, large intestine, liver, and spleen. Greater duration of treatment increased rumen, abomasum, duodenum, jejunum, large intestine, heart, liver, and spleen mass (P ≤ 0.05), but there was treatment by duration interaction (P ≥ 0.18). Interestingly, there was an interaction (P < 0.01) for jejunal and ileal length in response to treatment and duration. Length of each segment increased with duration of treatment for calves fed casein or glutamate but lengths decreased in calves fed control for greater amounts of time.